A study of awareness and factors affecting acceptance of PPIUCD in South-East Rajasthan - Sharma, Ashutosh; Gupta, Vinita (International Journal Of Community Medicine And Public Health, 2017)
Background: In spite of widely available choices for contraceptive method there is poor acceptance for the same because of less knowledge and ignorance. PPIUCD is one of best available contraceptive method which has potential to play a pivot role in country’s family planning programme. Present study is planned to find out awareness level and various factors affecting its acceptance among women in South-east Rajasthan. Methods: This was an observational study conducted in the department of Obstetrics and Gynaecology, Government Medical College and Jay Kay Lon Hospital, Kota between March 2013 and August 2014. Subjects were 18550 women visiting the centre for antenatal care and child birth. A preformed and predesigned semi structured questionnaire was applied to determine if these women were aware of the PPIUCD. Acceptability was defined as the number of antenatal women who agreed to undergo insertion of PPIUCD. Data was analyzed in Microsoft Excel 2010 & SPSS ver16. Results: Out Of 18550 women, only 480 (2.58%) were aware of the PPIUCD. The overall acceptability was found to be 2.94%. Safe and effective long term method makes PPIUCD a choice for acceptance. Conclusions: Level of awareness for PPIUCD was poor among women of south-east Rajasthan region. PPIUCD can play a pivot role in country’s family planning programme.